The sustainability of street vending as a livelihood strategy of women operating from Harare central business district - Mutize, Primrose (Midlands State University, 2017)
The purpose of this research was to examine the participation of women in street vending and then evaluate its sustainability as a livelihood strategy by women in Harare Central Business District. Livelihood indicators were used in evaluating sustainability and these include, food security, income levels, level and quality of education, ability to acquire assets and the health standards. A sample of 30 women from 5 selected vending sites were selected as respondents. The researcher used structured questioners and interviews in conducting the research. The findings were based on the information captured in the questioners and the interviews which were conducted face to face with the women. Women dominated the number of those in street vending in Harare CBD although man and youths were also in the streets. The participation of women in street vending managed to help women improve the poverty levels in their families. The income in families improved as compare to the period before street vending, but however the incomes were very small and differed with the goods at sell. In education women could now send their children to school but to acquire basic education and also using local schools that had lower fees. Food security in household improved and women and their families could now afford to eat at least 2meals per day. Healthy facilities became accessible, although it was basic and only local clinics. The participation of women in street vending has helped in improving the poverty levels of women but however cannot be sustainable as a livelihood strategy because of the challenges that cripple the vending system and that include, harassment from town officials, cheap and poor quality of good on sell, lack of proper infrastructure, lack of operating licenses discs and low demand and high competition.